Unifying activity, structure, and spectroscopy of [NiFe] hydrogenases: Combining techniques to clarify mechanistic understanding - Ash, PA; Kendall-Price, SET; Vincent, KA (American Chemical Society, 2019)
Achieving a unified understanding of the mechanism of a multicenter redox enzyme such as [NiFe] hydrogenase is complicated by difficulties in reconciling information obtained by using different techniques and on samples in different physical forms. Measurements of the activity of the enzyme, and of factors which perturb activity, are generally carried out using biochemical assays in solution or with electrode-immobilized enzymes using protein film electrochemistry (PFE). Conversely, spectroscopy aimed at reporting on features of the metalloclusters in the enzyme, such as electron paramagnetic resonance (EPR) or X-ray absorption spectroscopy (XAS), is often conducted on frozen samples and is thus difficult to relate to catalytically relevant states as information about turnover and activity has been lost. To complicate matters further, most of our knowledge of the atomic-level structure of metalloenzymes comes from X-ray diffraction studies in the solid, crystalline state, which are again difficult to link to turnover conditions. Taking [NiFe] hydrogenases as our case study, we show here how it is possible to apply infrared (IR) spectroscopic sampling approaches to unite direct spectroscopic study with catalytic turnover. Using a method we have named protein film IR electrochemistry (PFIRE), we reveal the steady-state distribution of intermediates during catalysis and identify catalytic “bottlenecks” introduced by site-directed mutagenesis. We also show that it is possible to study dynamic transitions between active site states of enzymes in single crystals, uniting solid state and solution spectroscopic information. In all of these cases, the spectroscopic data complement and enhance interpretation of purely activity-based measurements by providing direct chemical insight that is otherwise hidden. The [NiFe] hydrogenases possess a bimetallic [NiFe] active site, coordinated by CO and CN– ligands, linked to the protein via bridging and terminal cysteine sulfur ligands, as well as an electron relay chain of iron sulfur clusters. Infrared spectroscopy is ideal for probing hydrogenases because the CO and CN– ligands are strong IR absorbers, but the suite of IR-based approaches we describe here will be equally valuable in studying substrate- or intermediate-bound states of other metalloenzymes where key mechanistic questions remain open, such as nitrogenase, formate dehydrogenase, or carbon monoxide dehydrogenase. We therefore hope that this Account will encourage future studies which unify information from different techniques across bioinorganic chemistry.